Hábitos y creencias relacionadas con la salud en un grupo de adolescentes escolarizados de Bogotá (2005)
The purpose of this investigation is to describe the standards of beliefs concerning health/illness in a group of students in private schools Bogotá, and to determine its relation with the behavior of this population. Questionnaire CCHS-98 elaborated by GilRoales, it was applied to a group of students 14-18 years old, mostly from average social/economic status. According to the results, the sample presents a profile of medium to high risk in 66.8 percent, and a lesser experience relating to health in similar proportion (64.8 percent). Relation between profiles of risk and personal attribution toward smoking were encountered which indicates that even though a population tends to acquire the habit. The events are perceived as dependant upon personal factors which constitute a valuable recourse for prevention. The results make evident the factors of risk and protection in this population in particular, and these results can be useful in designing primary preventive programs for these young people. Index terms: beliefs, habits, risk profile, personal attribution, prevention.